The Coverage of Health Topics in Iraqi Press An analytical Study of Two Newspapers entitled 'al-Sabah and al-Mada' from January 1, 2007 to October 31, 2001 - جياد, محمد علي (ALBAHITH ALALAMI, 2017)
The current study aims to cover  the health topics  in the Iraqi  journalism ,  to know  the concern 's level  of the Iraqi journalism  when  covering  the health subjects and to know the size of its performance  under the diversity of  visual and audio medias. The researcher has discussed his research by wording it with a set of inquiries   that should be answered via the research and study.  He could have determined that by the following:What is the concern's level of Iraqi journalism over the health subjects?  What are the forms and press arts that are functionalized by the Iraqi journalism as to get the health message to the republics?  What is the source of these subjects?  What is the level  of Iraqi media 's interaction   with the  citizen  to address  his health  problems  and to  submit solutions  and addresses ?  The researcher has depended on the survey method and the study has been a descriptive one   for analyzing the content since it is considered as a basic part of the research. The researcher has depended on the two newspapers (   Al-Sabah and Al-Mada) for the period from January 1, 2007 up to October 31, 2007, since the general society of the research is the Iraqi media. The study   is concluded with the most prominent results:• News and  press reports  have occupied the first rank  in covering  the health topics  in  Al-Sabah and  Al-Mada"• The other  press arts  as investigations , press columns , advices , instructions , complains  and inquiries  are sub-concerned . This confirm to have both tend to news and reports and not to tend toward interpretation and explanation that concern   over the health problems.• The Iraqi journalism has not concerned over finding out solutions for the health problems for reasons that concerned over the policy of media   and the event in comparison with other events Iraq witnessed.• The Iraqi journalism are limitedly concerned over the complains columns and citizens' inquires   that shed the light on the   health problems.• The Iraqi journalism has brought up the negative side of health problems occurred in Iraq without resorting to the details and requirements. This matter refers not to depend on methods of how to healthily be educated.The study has discovered  that there has not been a coordination , follow up  and planning between the  local journalism from one side and   concerned offices from another side, as to cover stages of  breaking up or happening a health problem . This led to create a crisis of confidence and discrepancy in data, along with spreading horror and fear among the publics.